Media in human life – their role and significance for social development and functioning1 - Rugała, Hanna (Kultura-Społeczeństwo-Edukacja, 2021)
The media serve as a tool used for transmitting information, as well as a centre of social life. There is no doubt that over time they also became one of the most dominant areas of activity for children and young people. The paper aims to present the role and importance of the media in the lives of every human being, with particular emphasis on the young generation. The author takes a closer look at the media as an educational environment shaping society’s behaviour and way of thinking. The paper also outlines several examples of the impact and consequences that the use of mass media has on health and social functioning.